(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research aims to test the impact of the internal and external factors on the market value of the shares of traditional banks listed in the Damascus Securities Exchange during the period from (2011-2021 (. The sample included (11) traditional bank listed in the mentioned market. The internal factors were expressed through (share profitability, bank size, and trading size). External factors (inflation, gross domestic product growth rate, and political stability) as independent variables, while the market value of shares was the dependent variable and measured through the prices of divine close. To achieve the goal, the ARDL model methodology was used to test joint integration by relying on quarterly data of the type Panel, after conducting the unit root tests to ensure the stability of the time chains of the study variables. The research results showed a significant effect for all studied variables. While the effect was significant and inverse for trading volume, it was significant and positive for the remaining variables in the long run. In the short term, a significant inverse effect was found for earnings per share, and a significant and positive effect for trading volume and political stability. No effect was observed for the remaining variables on the market value of the studied bank shares.